The Influence of Book Creators on the Literacy and Numeracy Skills of Children Aged 5-6 Years - Ii Hartati; Asep Kurnia Jayadinata; Ii Hartati; Asep Kurnia Jayadinata (Jurnal Pembelajaran, Bimbingan, dan Pengelolaan Pendidikan, 2026)
This study aims to determine the effect of the use of Book Creator digital media on the literacy and numeracy skills of children aged 5–6 years. The study used a quasi-experimental method with a pretest-posttest nonequivalent control group design. The study subjects consisted of 30 children who were divided into an experimental group (n=15) and a control group (n=15). The experimental group learned using the Book Creator "Naya and Niko's Adventure to the Cheerful Village" for three meetings, while the control group used conventional learning. Literacy and numeracy ability data were collected using checklist observation sheets and analyzed through Shapiro-Wilk, Levene, Independent Sample t-Test, Mann-Whitney U Test, and N-Gain percentage. The results showed that there was a significant difference between the experimental group and the control group in literacy (p = 0.007) and numeracy (p = 0.017) skills. N-Gain analysis showed an increase in literacy ability in the experimental group by 38.48% and numeracy by 55.73%, higher than in the control group. These findings show that the use of Book Creator has a positive effect on the literacy and numeracy skills of children aged 5–6 years, with a higher effectiveness on numeracy skills. Media Book Creator can be an interactive digital learning alternative and in accordance with the characteristics of early childhood learning.